Education 4.0: Pergeseran pendidikan sebagai konsekuensi revolusi industri 4.0 - Pratidhina, Elisabeth (Universitas Negeri Yogyakarta, 2020)
Industrial Revolution 4.0 is changing how we live, work, and communicate. The education field should develop to adapt to the revolutionary changes that happen in the world recently. Industrial revolution 4.0 makes shifted paradigm in education. Education 4.0 is the desired approach to learning that aligns itself with the emerging fourth industrial revolution. It brings up the well-known educational concepts such as self-directed learning and long-life learning. This paper discuss shifting educational theory in Education 4.0 and the phenomenon of the emerging new education technology which attempts to fill the need for self-directed learning dan long-life learning.